Fabrication and Evaluation of a pH-Responsive Nanocomposite-Based Colonic Delivery System for Improving the Oral Efficacy of Liraglutide - Song JG; Kim DH; Han HK (International Journal of Nanomedicine, 2023)
Jae Geun Song,* Da Hyun Kim,* Hyo-Kyung Han BK21 FOUR Team and Integrated Research Institute for Drug Development, College of Pharmacy, Dongguk University-Seoul, Goyang, 10326, Korea*These authors contributed equally to this workCorrespondence: Hyo-Kyung Han, BK21 FOUR Team, College of Pharmacy, Dongguk University-Seoul, Dongguk-ro-32, Ilsan-Donggu, Goyang, 10326, Korea, Tel +82-31-961-5217, Fax +82-31-961-5206, Email hkhan@dongguk.eduPurpose: Oral administration of liraglutide, a protein drug, suffers from low intestinal absorption and instability in the gastrointestinal tract, resulting in low bioavailability. The present study aimed to develop a pH-responsive nanocomposite based-colonic delivery system to improve the oral efficacy of liraglutide.Methods: Nanocomplex (AC-Lira) between aminoclay and liraglutide was prepared by a spontaneous self-assembly. After surface charge reversal using citric acid, AC-Lira was coated with poly(methacrylic acid-co-methyl methacrylate) (1:2). The fabricated nanocomplex underwent various in vitro studies to characterize its physicochemical properties, drug release, and cellular transport. In vivo efficacy studies were also conducted using streptozotocin-induced diabetic rats.Results: Both uncoated (AC-Lira) and coated nanocomplex (EAC-Lira) achieved high entrapment efficiency (> 90%) and showed a narrow size distribution. While exhibiting low drug release at pH 1.2 (approximately 30%), EAC-Lira achieved rapid and extensive drug release (~90%) at pH 7.4, displaying pH-dependent drug release. EAC-Lira showed significant size reduction and surface charge reversal during dissolution at pH 7.4, probably due to the removal of the outer coating layer. Furthermore, EAC-Lira was effective at protecting the entrapped proteins against enzymatic degradation. EAC-Lira also increased the membrane transport of liraglutide by 3.5 folds in Caco-2 cells. Owing to enhanced membrane transport and metabolic stability, EAC-Lira improved in vivo efficacy of orally administered liraglutide, significantly reducing blood glucose concentrations, intake of food and water, and body weight in type 2 diabetes rats.Conclusion: These results suggest EAC-Lira is a promising approach to improving the oral bioavailability and efficacy of liraglutide.Keywords: liraglutide, aminoclay, GLP-1 agonist, type 2 diabetes, nanocomposite